2020
DOI: 10.3390/catal10090985
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Photocatalyzed Chlorophenols for Sequential Photocatalytic-Biological Treatment Optimization

Abstract: Given the known adverse effect of chlorophenols for the aquatic environments which they can reach, the development of efficient methods both technically and economically to remove them has gained increasing attention over time. The combination of photocatalytic oxidation with biological treatment can lead to high removal efficiencies of chlorophenols, while reducing the costs associated with the need to treat large volumes of aqueous solutions. Therefore, the present paper had as its main objective the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The second one involves a direct attack of the hydroxyl radicals which would lead to the displacement of chlorine from the para position with the formation of 2-chloro-4-hydroxyphenol. Next, there may be a successive attack of the hydroxyl radicals until the benzene ring is open, or there may be a first attack of the nascent hydrogen on the chlorine from the ortho position with the formation of hydroxyquinone followed by the successive attack of hydroxyl radicals until the opening of the benzene ring [9,32]. However, it appears that both degradation mechanisms are strongly influenced by the pH of the aqueous solution, and therefore these are in good agreement with the results found in this work.…”
Section: Influence Of Hydrogen Peroxide/organic Carbon Molar Ratiomentioning
confidence: 99%
“…The second one involves a direct attack of the hydroxyl radicals which would lead to the displacement of chlorine from the para position with the formation of 2-chloro-4-hydroxyphenol. Next, there may be a successive attack of the hydroxyl radicals until the benzene ring is open, or there may be a first attack of the nascent hydrogen on the chlorine from the ortho position with the formation of hydroxyquinone followed by the successive attack of hydroxyl radicals until the opening of the benzene ring [9,32]. However, it appears that both degradation mechanisms are strongly influenced by the pH of the aqueous solution, and therefore these are in good agreement with the results found in this work.…”
Section: Influence Of Hydrogen Peroxide/organic Carbon Molar Ratiomentioning
confidence: 99%
“…The latter appear to be capable of interacting with molecular oxygen yielding peroxo species thus providing an extended light-induced "self-cleaning" behavior. The combination of photocatalytic oxidation with biological treatment as studied by Liliana Bobirica and her colleagues was found to lead to high removal efficiencies of chlorophenols, while reducing the costs associated with the need to treat large volumes of aqueous solutions [3]. It could be shown that, regardless of the concentration of chlorophenol and its type, the working solutions become readily biodegradable following an initial irradiation by ultraviolet light with this irradiation period representing at most half of the total irradiation period necessary for the complete mineralization of the working solutions.…”
mentioning
confidence: 99%